Dark matter, CEνNS and neutrino new physics scrutinized by a statistical method in Xenon-based experiments - Jian Tang; Bing-Long Zhang (Journal of High Energy Physics)
Abstract Dark matter direct detection experiments are approaching the neutrino floor, with a significant probability of measuring coherent elastic neutrino-nucleus scattering (CEνNS) and exploring potential neutrino-related new physics (νNP). In the present study, the simultaneous presence of dark matter and νNP is emphatically investigated, revealing a response similar to Standard Model neutrino backgrounds in Xenon-based dark matter experiments. Through analyses of three U(1) extension models, it is determined that dark matter signals can be differentiated from an excess or a depletion of neutrino contributions from νNP by applying a statistically defined distinction method to nuclear and electronic recoil spectra. Additionally, an investigation is conducted into how νNP affects the exclusion limits for spin-independent dark matter-nucleon interactions. The present findings could facilitate the identification of new physics in future dark matter experiments.